Utilities of Peripheral Nerve Blocks beyond the Operating Room: A Narrative Review - Krishna Prasad GV (Academia Anesthesiologica International, 2020)
Intravenous analgesia has been the standard method employed to alleviate pain. However, intravenous analgesia cause higher rate of systemic side-effects, patient discomfort and longer hospital stays. In recent times, peripheral nerve blocks (PNB) have become the most preferred choice for a variety of procedures in operating room. PNBs lower the risks of peri-operative challenges, they involve in lowering the number of opioid-related complications, and they mitigate the need for general anaesthesia. Further, peripheral nerve blocks with the assistance from ultrasound technology provide superior choices over traditional pain-relieving methods practiced in the operating room. Objective of the current review article is to throw light on the peripheral nerve blocks and their utilities other than operation theatres. Also, this review article throws light on the several utilities of peripheral nerve blocks in trauma cases, block on arrival, upper limb, lower limb, chest and abdomen, head injury, maxillofacial injuries, uses in central vein canulations, recurrent ventricular tachycardia, interventional radiology, chronic pains with acute presentation and gangrene of limbs.